PENERAPAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN ILMU PENGETAHUAN ALAM SISWA KELAS V SD NEGERI SURO - Reno Nopendra; Asep Sukenda Egok; Riduan Febriandi (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aims to determine the results of class V SD Negeri Suro science learning after the application of the Problem Based Learning model. This study uses quasi-experimental. The population is all students in grade V SD Negeri Suro for the academic year 2020/2021, totaling 16 students taken as the sample, which is class V with 16 taken with saturated sampling technique. The data collection technique used was a test technique in the form of a description of 10 questions. The collected data were analyzed using the -Z test. Based on the results of the Z-test analysis of the final test data at the significant level α = 0.05, it can be concluded that the science learning outcomes of grade V SD Negeri Suro students after the application of the Problem Based Learning model are significantly complete. The average final test score was 84.38 with a percentage of the number of students who completed 93.75% and the hypothesis testing was obtained by (8,23) ≥. Keywords: Application, Science Learn